Civil service reform in Afghanistan since 2018: a case study of E- recruitment system in independent administrative reform and civil service commission - Habibullah (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2020.